2020
DOI: 10.1007/s40544-020-0458-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact geometry on the friction of acrylamide hydrogels with different surface structures

Abstract: Polyacrylamide (PAAm) hydrogels with brush-covered or crosslinked surfaces were produced and their tribological behavior was studied over a wide range of sliding speeds for two different contact geometries: sphere-on-flat and flat-pin-on-flat. Irrespective of the contact geometry, the brushy hydrogel surfaces displayed up to an order of magnitude lower coefficients of friction μ (COF) compared to the crosslinked surfaces, even achieving superlubricity (μ < 0.01). In general, a hydrogel sphere showed a lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
1
15
1
Order By: Relevance
“…33 It is important to note, however, that despite the differences at the surface glass-and PS-molded gels have a similar bulk structure. 30 As expected, we again confirmed that different molding materials result in hydrogels with different surface structures, however, surface treatment and thus the hydrophobicity of the molding surface appears to have no significant effect on the surface structure of the synthesized hydrogels.…”
Section: Hydrophobicitysupporting
confidence: 84%
See 3 more Smart Citations
“…33 It is important to note, however, that despite the differences at the surface glass-and PS-molded gels have a similar bulk structure. 30 As expected, we again confirmed that different molding materials result in hydrogels with different surface structures, however, surface treatment and thus the hydrophobicity of the molding surface appears to have no significant effect on the surface structure of the synthesized hydrogels.…”
Section: Hydrophobicitysupporting
confidence: 84%
“…The extracted elastic modulus was 30 kPa ± 1 kPa for both glass-molded hydrogel surfaces. In the past, the elastic moduli of similar glass-molded hydrogels were also measured using microindentation 29 and macroindentation 30 , which showed a good agreement with both the Hertzian and the Winkler contact models. With both these models assuming a homogenous structure, glass-molded hydrogels appear to have a homogeneous polymer density profile throughout their thickness.…”
Section: Hydrophobicitymentioning
confidence: 83%
See 2 more Smart Citations
“…erefore, the development of alternative lubrication methods to increase the service life of artificial joints has attracted considerable attention [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%